The ethical challenges of personalized digital health - Maeckelberghe, Els; Zdunek, Kinga; Marceglia, Sara; Farsides, Bobbie; Rigby, Michael (Frontiers in Medicine, 2023)
Personalised digital health systems (pHealth) bring together in sharp juxtaposition very different yet hopefully complementary moral principles in the shared objectives of optimising health care and health status of individual citizens, while maximising the application of robust clinical evidence, through harnessing powerful and often complex modern data handling technologies. Principles brought together include respecting the confidentiality of the patient – clinician relationship; the need for controlled information sharing in teamwork and shared care; benefitting from healthcare knowledge obtained from real-world population-level outcomes; and recognition of different cultures and care settings. This paper outlines the clinical process as enhanced through digital health; reports on examination of the new issues raised by computerisation of health data; outlines initiatives and policies to balance harnessing of innovation with control of adverse effects; and emphasises the importance of context of use and of citizen and user acceptance. The importance of addressing ethical issues throughout the life cycle of design, provision, and use of a pHealth system is explained, and a variety of situation-relevant frameworks presented, to enable a philosophy of responsible innovation, matching best use of enabling technology with creation of a culture and context of trustworthiness.